PENDAMPINGAN PASAR TRADISIONAL AMERTHA SEDANA DESA ADAT MENGWITANI KECAMATAN MENGWI KABUPATEN BADUNG MENUJU PASAR SEHAT - Suyasa, I Nyoman Gede; Rusminingsih, Ni Ketut (Jurnal Pengabmas Masyarakat Sehat, 2023)
Amertha Sedana traditional market is a market managed by the Mengwitani Traditional Village with an area of approximately 43 acres, located on the Denpasar-Gilimanuk route. This market is open every day from 04.00 – 11.00 WITA in the morning and in the afternoon it is open from 15.00 to 22.00 WITA. Based on preliminary information, the traders who occupy the 2 main buildings consist of 42 kiosks, 71 stalls and 15 seasonal traders and 22 sengol traders. Priority problems that need to be solved Increasing knowledge of traders and visitors through health education with booklet media and giving masks to traders and visitors. Addition of temporary garbage shelters at each end of the stall. Addition of portable handwashing stations and hand sanitizers in strategic places before visitors and traders enter the market. The service method is by observing the Amertha Sedana traditional market, Mengwitani Traditional Village. Conduct an assessment before the service treatment is carried out on the health level of the traditional market. After the service is carried out, an assessment of the health of the market is carried out again. The target audience is managers, traders and visitors to traditional markets with working procedures. Prior to the assistance, a healthy market was infected using the Indonesian Ministry of Health's Decree No. 519/Menkes/SK/VI/2008 on traditional markets in Mengwi District. After the infection has identified the market sanitation problems that are still lacking, then assistance is provided to managers, traders and visitors. Furthermore, the level of market infection is measured after mentoring is carried out. The health level of Amertha Sedana Traditional Market in terms of market location, market buildings, sanitation, PHBS, security and other facilities in the market is generally healthy. Before each mentoring there was a clean and healthy living behavior of traders and penjung who were still not healthy, after mentoring by providing booklets, sinks and masks there was a change in clean and healthy living behavior into the behavior of traders and visitors in the healthy category. The total value of the Mengwi market health score is 6571 including healthy after mentoring the Amerta Sedana market health score in the Mengwitani Traditional Village to 7436 so that there is an increase of 865